2003
DOI: 10.1074/jbc.m302364200
|View full text |Cite
|
Sign up to set email alerts
|

p53 Activation in Adipocytes of Obese Mice

Abstract: The tumor suppressor p53 is a transcription factor that activates or represses its target genes after various genotoxic stresses. We have previously shown that sterol regulatory element-binding protein-1 (SREBP-1), a key transcriptional regulator of triglyceride synthesis, and the lipogenic enzymes under its control are markedly suppressed in adipocytes from genetically obese ob/ob mice. Here we demonstrate that p53 and its target genes are highly induced in adipocytes of ob/ob mice in a fed state, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
193
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(203 citation statements)
references
References 49 publications
8
193
0
2
Order By: Relevance
“…For example, increased circulating MIC-1 levels may reflect p53 pathway activation (24). This pathway may, among other important functions, play a role in the pathophysiology of obesity (25). Furthermore, MIC-1 expression is one of genes responsible for initiating the process of stimulus-induced adaptive changes (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased circulating MIC-1 levels may reflect p53 pathway activation (24). This pathway may, among other important functions, play a role in the pathophysiology of obesity (25). Furthermore, MIC-1 expression is one of genes responsible for initiating the process of stimulus-induced adaptive changes (26).…”
Section: Discussionmentioning
confidence: 99%
“…Yahagi et al (2003) demonstrated that p53 and its target genes are highly induced in adipocytes of ob/ob mice in a fed state, leading to the negative regulation of lipogenic genes (Yahagi et al 2003). Moreover, disruption of p53 in ob/ ob mice fully suppressed the p53-regulated genes to the levels of wild-type subjects and partially restored expression of lipogenic enzymes.…”
Section: P53mentioning
confidence: 99%
“…Moreover, disruption of p53 in ob/ ob mice fully suppressed the p53-regulated genes to the levels of wild-type subjects and partially restored expression of lipogenic enzymes. The authors suggested that the activation of the p53 gene might develop a negative feedback loop against abnormal fat accumulation in adipocyte cells (Yahagi et al 2003). Another study on rodents showed that p53 expression in AT is a key component in the development of insulin resistance, which underlies age-related cardiovascular and metabolic disorders (Minamino et al 2009).…”
Section: P53mentioning
confidence: 99%
“…18 This multitask protein may either induce or suppress key differentiation factors depending on the specific cellular fate. 19 Although increasing evidence from in vitro and in vivo studies suggest that p53 exerts a negative effect on white adipogenic differentiation, 19,20,21 its role in brown fat differentiation has not been determined.…”
mentioning
confidence: 99%